converting polar equation to cartesian equation

With this problem it ask to convert r=-3 cos(theta) from polar form to cartesian

This is what I get

$\displaystyle

\begin{array}{l}

r = - 3\sin (\theta ) \\

(x - \frac{3}{2})(x - \frac{3}{2}) + (\frac{{ - 3}}{2})^2 + y^2 = 0 + (\frac{{ - 3}}{2})^2 \\

(x - \frac{3}{2})^2 + (\frac{{ - 3}}{2})^2 + y^2 = (\frac{{ - 3}}{2})^2 \\

\end{array}

$

However the answer given is as below. What have I done wrong?

$\displaystyle

(x - \frac{3}{2})^2 + y^2 = (\frac{{ - 3}}{2})^2 \\

$